EFFECT OF COAL UPGRADING ON RHEOLOGY OF COAL WATER MIXTURE - DATIN F. UMAR; BUKIN DAULAY; HIROMOTO USUI; YOSHIYUKI KOMODA (Indonesian Mining Journal, 2007)
Coal water mixture (CWM) is coal-water slurry in which particles of coal with a certain particle size distribution are suspended in water. CWM is required to have the highest possible coal concentration and a moderate viscosity in order to make handling easy. The main purpose of this study is to obtain the effect of coal upgrading on the rheology of CWM in terms of finding the most suitable dispersing additive in producing CWM with highest coal concentration. Two kinds of coal, raw and upgraded coal, from three areas in Indonesia have been used. Three kinds dispersing additives, i.e. formalin conden- sation product of naphthalene sulfuric acid (NSF), polystyrene sulfonic acid (PSS) and poly (meth) acrylate (PMA) were tested to produce CWM with good flow characteristics. The rheology of CWM was prepared, measured by a stress control type rheometer (Rheometric Scientific Co. Ltd., SR-5) in steady shear mode at 25ºC. The apparent viscosity of upgraded coals showed a better slurry-ability of CWM as a function of coal concentration for every dispersing additive compared to the raw coal.